The best practices of human rights (Atham) programme in selected secondary schools in Malaysia - Chang Lee Hoon, Teng Jane, Yan Fang, Bucher Stefan, Basiran Nurhuda, Hussin Nafisah Ilham, Boyman Siti Norainizahhafizah, (N/A, 2013)
The best practices of human rights (Atham) programme in selected secondary schools in Malaysia by Chang Lee Hoon, Teng Jane, Yan Fang, Bucher Stefan, Basiran Nurhuda, Hussin Nafisah Ilham, Boyman Siti Norainizahhafizah,